PENGEMBANGAN E-LKPD BERBASIS MIND MAPPING PADA MATERI SIKLUS HIDUP HEWAN KELAS IV SEKOLAH DASAR - Mei lani; Nyiayu Fahriza Fuadiah; Patricia H.M Lubis (Jurnal Holistika, 2023)
This research aims to produce a product in the form of mind mapping-based e-LKPD (electronic- Lembar Kerja Peserta Didik)  for grade IV elementary school science learning. There were problems found, namely that teachers did not have innovative teaching resources, still used conventional methods, and there were still students who had not reached the KKM scores that had been set by the school. This researcher and development uses the Research and Development method using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The subjects in this research were class IV students at SDN 136 Palembang. Data collection instruments are in the form of questionnaires and documentation. Data analysis in this research is to obtain validity, practicality and effectiveness. This research and development produced an e-LKPD that was valid to use, with a score of 89% in the "Very Valid" category based on the results of one-to-one trials and small groups obtained a score of 89.2% in the "Very Practical" category. As well as the effectiveness value of the learning outcomes, the percentage obtained was 82.75%, so it can be concluded that the e-LKPD developed is valid, practical and effective for use as teaching material in learning.Keywords: e-LKPD, Mind Mapping, ADDIE